Position Paper of the European Society of Cardiology Working Group Cellular Biology of the Heart: cell-based therapies for myocardial repair and regeneration in ischemic heart disease and heart failure - Madonna, Rosalinda; Van Laake, Lindaw.; Davidson, Sean M.; Engel, Felix; Hausenloy, Derek J.; Lecour, Sandrine; Leor, Jonathan; Perrino, Cinzia; Schulz, Rainer; Ytrehus, Kirsti; Landmesser, Ulf; Mummery, Christine L.; et al. (European Heart Journal, 2016)
Despite improvements in modern cardiovascular therapy, the morbidity and mortality of ischaemic heart disease (IHD) and heart failure (HF) remain significant in Europe and worldwide. Patients with IHD may benefit from therapies that would accelerate natural processes of postnatal collateral vessel formation and/or muscle regeneration. Here, we discuss the use of cells in the context of heart repair, and the most relevant results and current limitations from clinical trials using cell-based therapies to treat IHD and HF. We identify and discuss promising potential new therapeutic strategies that include ex vivo cell-mediated gene therapy, the use of biomaterials and cell-free therapies aimed at increasing the success rates of therapy for IHD and HF. The overall aim of this Position Paper of the ESC Working Group Cellular Biology of the Heart is to provide recommendations on how to improve the therapeutic application of cell-based therapies for cardiac regeneration and repair.
EVALuna2:25529